Islamic Law as An Umbrella of Human Rights in The Loss of Social Welfare Rights of Pedicab Drivers towards The Existence of Online Transportation - Novemyanto, Alfin Dwi; Hani, Aisiyah Puspita (Journal International Dakwah and Communication, 2023)
With change mode transportation become online transportation, the result in low enthusiasts’ transportation conventional yet digitally based pedicab driver in a few areas. This resulted hurt their right human on pedicab drivers and no its implementation justice social on the precepts fifth Pancasila. The method in this research is descriptive qualitative method with using a systematic technique literature review. Existence pedicab drivers that lost it source income because presence mode online transportation, that is case hurt their right in fulfillment worker's welfare pedicab drivers and necessary exists breakthroughs, modifications, and renewals will be existing policies and regulations from to fit with phenomenon social happenings. It has confirmed in Article 27 Paragraph 2, Article 28 A, Article 28C paragraph (1), and Article 28D paragraph (1) of the 1945 Constitution, Surah As- Syuara verse 183 and Surah Al- Qashash Verse 77 as base changes and reminders about must followed and made policy new orgive protection rights attached to the pedicab drivers for the sake of achieving it fairness, usefulness, and certainty law.